Influence of the development of graphic techniques on art in Ukraine - O. L. Khramova-Baranova; I. O. Yakovets (History of science and technology, 2018)
The article reveals the importance of the development of graphic techniques as means of artistic and figurative expressiveness in art and design in Ukraine.  The study examined some graphic techniques as a means of graphic expressiveness and analyzed the use of these techniques in order to use them in various types of design, as well as to uncover the creative potential of the artist, the graphic designer.  It is worth noting that to date there is little research on this issue, and individual studies do not fully reflect the influence of graphic techniques on the development of visual art and design.  The purpose of the research is the need to revive and popularize graphic techniques, effectively selecting them as means of graphic expression in art and design.  The lack of knowledge of the formation and development of graphic techniques, their great importance and role in asserting the expressiveness of the artistic image determine the relevance of the topic. Analyzed the historiography of the problems and proved that the research of the formation and development of graphic techniques involved several scientists.  A great contribution to the development of these issues was made by such specialists as A.A. Leshchinsky, V.A.Favorsky, M.Yu.Miroshina, N.N.Samoylova and others. The research methodology is based on the universal principles of scientific knowledge - historicism and scientific objectivity, as well as on the wide use of comparative historical, systemic methods.  Graphics is a type of visual art that uses line, stroke and spot as the main graphic tools, and the compositional nature of the linear-graphic form depends on the material and technique of the performance.  Depending on the method of implementation and the possibilities of replication, the graphics are divided into author's (original works of unique graphics), printmaking (types of artistic printing), and massively printed products.  It can be argued that the graphics technology has undergone significant changes compared with the time of their formation.  At the beginning of the XXI century, their technology becomes more complex and the texture of the print and the color scheme become more complicated.  Today uses abstract, futuristic forms, the most inherent improvisational art.  The development of graphic techniques in this direction provides bright creative solutions.  Modern artists continue to search for new tools and techniques for enriching graphic techniques.  Today, easel graphics is not a process of mechanical mass prints, it requires a live direct participation of the creator from the first to the last minute of the birth of the artwork.